If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(2-7)=6(c-7)
We move all terms to the left:
6(2-7)-(6(c-7))=0
We add all the numbers together, and all the variables
-(6(c-7))+6(-5)=0
We add all the numbers together, and all the variables
-(6(c-7))-30=0
We calculate terms in parentheses: -(6(c-7)), so:We get rid of parentheses
6(c-7)
We multiply parentheses
6c-42
Back to the equation:
-(6c-42)
-6c+42-30=0
We add all the numbers together, and all the variables
-6c+12=0
We move all terms containing c to the left, all other terms to the right
-6c=-12
c=-12/-6
c=+2
| -2(c-2)=-2(c-6) | | 6(v-8)=6(v-6) | | 6x-8x-4=12 | | 4(x+6)=4(x+7) | | 8n-5=-19(12+n) | | 8a+12=80 | | 10x-8=20-14x | | V=1/3πr^2 | | 6f=-66 | | 5(x+5)=5x-1 | | 5n+-4n=5 | | -12+2x=-14 | | 5-x-x=- | | 3v-42=5(v-6) | | 2n-13=-19(16+4n) | | a/9=1/23 | | 289=69-u | | 2(x-2)=5x-16 | | -30=12-6x | | 5/8=3/y | | 6x+12+7x=-4 | | -2(x^2-7)^2+3=-47 | | 4(k+9)=4(k+9) | | −4−0.2x+11=−0.8x+10 | | 5x−7=58 | | −4−0.2x+11=−0.8x+10 | | 5x−2=3x+1 | | 12=0.005x | | 116(x−40)=5+x | | 11-3a+6=27 | | 5(x−2)=3x+1 | | 6(x+6)=6x+4 |